Clinical utility of synuclein skin biopsy in the diagnosis and evaluation of synucleinopathies - Isaacson, Jonathan R.; Freeman, Roy; Gibbons, Christopher H. (Frontiers in Neurology, 2024)
IntroductionThe diagnosis of diseases known as synucleinopathies, Parkinson’s disease (PD), multiple system atrophy (MSA) and Lewy body dementia (DLB), is predominantly based on clinical criteria. However, diagnostic uncertainty may persist until late in the disease process leading to delays in diagnosis and medical mismanagement. Skin biopsy detection of phosphorylated alpha-synuclein (P-SYN) is a sensitive and specific technique that increases diagnostic sensitivity of synucleinopathies, although the clinical utility of this test has not been fully explored.MethodsTo determine the role of skin biopsy in the diagnosis of synucleinopathies we performed a retrospective chart review of patients who underwent skin biopsy for detection of P-SYN in the evaluation of neurodegenerative disease at a tertiary care academic institution to investigate the change in diagnosis and medical management based on the results of skin biopsy detection of P-SYN.ResultsWe included 97 patients suspected to have a synucleinopathy: 54 with PD, 19 with DLB and 24 with MSA. After skin biopsy testing for P-SYN, 78% of patients had a change in their clinical care with 66% having a change in their diagnosis and 55% having a change in their treatment. Changes in diagnosis were most common in patients with parkinsonism with prominent action tremor (93%), lower-extremity predominant parkinsonism (postural instability and gait dysfunction) (90%), and parkinsonism with predominant cognitive dysfunction (76%).DiscussionIn patients with suspected synucleinopathies, skin biopsy detection of P-SYN had a high level of clinical utility leading to changes in clinical diagnosis and treatment.